Government Employment and Wages and Labor Market Performance - Kontolemis, Zenon; Demekas, Dimitri (Washington, D.C. : International Monetary Fund, 1999)
Government wage, benefit, and employment decisions are not taken on a profit-maximizing basis and have a substantial impact on aggregate labor market performance and unemployment. In a two-sector labor market model with free mobility of labor, an increase in government wages or benefits reduces private sector employment, and government employment is not an effective counter-cyclical instrument. Empirical tests for Greece confirm that the expansion of the public sector in the 1980s contributed to the deterioration of labor market performance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet